2015
DOI: 10.1136/sextrans-2015-052216
|View full text |Cite
|
Sign up to set email alerts
|

‘It's all in the message’: the utility of personalised short message service (SMS) texts to remind patients at higher risk of STIs and HIV to reattend for testing—a repeat before and after study: Table 1

Abstract: Sending a personalised text message with increased contact information as a reminder for retesting increased reattendance rates by 23% in patients who are at higher risk of STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 10 publications
2
47
2
Order By: Relevance
“…We did not find any evidence to suggest that the primer message had a positive independent effect on kit return in our study. Research in a UK sexual health clinic found that simply sending SMS messages to patients to encourage re‐attendance had no effect but that the addition of a more personalized message with a patient's name resulted in higher rates of re‐attendance . In contrast, names were already included in the standard service in our study, which may explain the lack of the effect we observed.…”
Section: Discussioncontrasting
confidence: 67%
“…We did not find any evidence to suggest that the primer message had a positive independent effect on kit return in our study. Research in a UK sexual health clinic found that simply sending SMS messages to patients to encourage re‐attendance had no effect but that the addition of a more personalized message with a patient's name resulted in higher rates of re‐attendance . In contrast, names were already included in the standard service in our study, which may explain the lack of the effect we observed.…”
Section: Discussioncontrasting
confidence: 67%
“…The study of appointment reminders has occurred in a variety of settings, including primary care ( Steiner et al, 2016 ), dental care ( Perry, 2011 ), and psychotherapy clinics ( Delgadillo et al, 2015 ). Appointment attendance reminders were found to either increase the rate of appointment attendance, increase the rate of appointments cancelled ahead of time, or decrease the rate of missed appointments in 48 of the 56 studies (86%) ( Altuwaijri et al, 2012 ; Arora et al, 2015 ; Berenson et al, 2016 ; Bourne et al, 2011 ; Brannan et al, 2011 ; Branson et al, 2013 ; Chen et al, 2008 ; da Costa et al, 2010 ; Deng et al, 2015 ; Downer et al, 2005 ; Fairhurst and Sheikh, 2008 ; Farmer et al, 2014 ; Foley and O'Neill, 2009 ; Geraghty et al, 2008 ; Hofstetter et al, 2015a , Hofstetter et al, 2015b ; Kerrison et al, 2015 ; Koshy et al, 2008 ; Leong et al, 2006 ; Liew et al, 2009 ; Lin et al, 2012 ; Liu et al, 2017 ; Lund et al, 2012 ; Lund et al, 2014 ; McInnes et al, 2014 ; Milne, 2010 ; Muller et al, 2017 ; Murray et al, 2015 ; Narring et al, 2013 ; Nundy et al, 2013a , Nundy et al, 2013b ; Nyatsanza et al, 2016 ; Odeny et al, 2012 ; Perry, 2011 ; Pijnenborg et al, 2007 ; Prasad and Anand, 2012 ; Pratap et al, 2015 ; Rohman et al, 2015 ; Sims et al, 2012 ; Sly et al, 2014 ; Steiner et al, 2016 ; Taylor et al, 2012 ; Thomas et al, 2017 ; Ting et al, 2012 ; Tolonen et al, 2014 ; Trent et al, 2015 ; …”
Section: Resultsmentioning
confidence: 99%
“…The most active strategy, that is, when an appointment was scheduled in advance and a reminder sent, was the most successful. The higher success of this strategy compared to the other experimental strategy may be partly because reminders were sent earlier, the content of the SMS reminder was more personalised or calling participants was more effective than SMS [12] although, by design, the specific contribution of these components of the intervention could not be assessed. Interestingly, only 8% (17/218) confirmed the appointment by SMS reply, while 27% (59/218) confirmed it after receiving the subsequent phone call.…”
Section: Discussionmentioning
confidence: 99%
“…SMS reminders also have the potential to increase the uptake of frequent HIV testing in uninfected at‐risk individuals [9]. However, previous studies had limitations: they either were observational [10‐12] or assessed the effect of sending SMS reminders to retest participants presenting with a suspected acute HIV infection one month after a first negative test, a very specific situation [13].…”
Section: Introductionmentioning
confidence: 99%